SPORTSHÍLARDÍŃ ULÍWMA HÁM ARNAWLÍ TAYARLÍQLARÍNÍŃ FORMALARÍ - Utepbergenov, A.K.; Bekmurzaev, A.K. (ILIM hám JÁMIYET, 2025)
The article talks about the main directions of preparation for sports activities, improvement of organs, systems and functions in the process of physical activity and at the same time enriching any of its activities and experience.